Study and Improvement of Halal Travel Routes linked to Neighboring Countries under the Indonesia-Malaysia-Thailand Growth Triangle: IMT-GT - Luxchaigul, Nat; Bunnag, Saranya; Malyarom, Mongkon (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
This study was employed quantitative and qualitative methods., had the Abstract This study employed quantitative and qualitative methods and aimed to examine and develop routes for halal traveling in the five southern bordered provinces in order to connect land transports air transport within Thailand, Malaysia, and Indonesia; to develop halal traveling programs by designing the types of traveling within the five southern bordered provinces in accordance with the tourists’ wants in the forms of both text descriptions and maps, to investigate the perceptions of tourists both Thais and foreigners towards the attractive places of the halal traveling routes which connected within the five southern bordered provinces, Indonesia and Malaysia; to examine the necessity of traveling sites development and facilities for traveling through the halal traveling routes which connected within the five southern bordered provinces, Indonesia and Malaysia; to study laws, restrictions, agreements, cooperation framework, and other disciplines relevant to ASEAN Free Trade Area (AFTA) and cooperation of IMT-GT that obstructed Halal tourism in Thailand, Malaysia, and Indonesia. The purposive samplings population and methods of the research involved the following: 50 head staff working in tourism, 150 Muslim tourists both Thais and foreigners, and 150 people living in the contexts of traveling places . In-depth interview and content analysis were used in the study. The results showed that 1) The routes development for traveling in the five southern bordered provinces connected among land transport (trains and cars), water transport, and air transport within Thailand, Malaysia, and Indonesia ; 2) The Halal tours were designed for 43 traveling programs to respond the tourists’wants in terms of text descriptions and maps ; 3) The survey of tourists found that according to the survey of tourists traveling in the five southern bordered provinces, the attractive places the tourists were mostly interested were in the Hot Spring in Yala, Had Chalathat and the Muslim tourists considered the worthiness of the traveling sites in terms of their popularity / well- known such Ban Wat Ancient City (Pattani), Pikulthong Garden (Narathiwat); 4) More than 80% of the Muslim tourists found the problems and obstacles while traveling such lack of Halal tourism information, Prayer rooms were not available at the traveling sites, None of Islamic transportation systems provided, etc. and 5) Have the legislative acts relevant to Halal tourism that should stress cooperation framework, rules and disciplines under the cooperative framework of Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) Keywords: Halal Travel Routes Development, Halal tourism, Legislative Acts, Indonesia-Malaysia- Thailand Growth Triangle (IMT-GT),